Lee's legacy - Chan, Fiona (Singapore : Straits Times Press, 2015)
Compiled for the first time in Lee's Legacy, this selection of incisive viewpoints displays a wide range of perspectives on Mr Lee's contributions to Singapore and beyond, spanning the sustainability and applicability of the'Singapore model' to Mr Lee's influence on the policies of foreign countries. The result is a thought-provoking anthology of presents a balances overview of the complex and far-reaching legacy of Mr Lee Kuan Yew.
'This book was made possible by Bank of Singapore.'
Keywords: Lee, Kuan Yew, -- 1923-2015 -- Anecdotes; Prime ministers -- Singapore -- Anecdotes; Funeral rites and ceremonies -- Singapore; Singapore -- Politics and government